Pengaruh Pengetahuan Auditor, Pengalaman Auditor, Kompleksitas Tugas, Locus Of Control, Tekanan Ketaatan Dan Senioritas Auditor Terhadap Audit Judgment - Linda Ayu Lestari; Hadi Mahmudah; Neneng Lasmita Susanti (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
This study aims to determine the effect of auditor knowledge, auditor experience, task complexity, locus of control, obedience pressure and auditor seniority on audit judgment. The method used is descriptive quantitative. The data used is the data of auditors who work at Public Accounting Firms (PAC) in Bekasi and Jakarta. The technique of using data is by distributing questionnaires. The data was processed using SPSS version 25. The results showed that the auditor’s knowledge had an effect on audit judgment. Meanwhile, auditor experience, audit complexity, locus of control, obedience pressure and auditor seniority have no effect on audit judgment. Keyword: Audit Judgment, Auditor Knowledge, Auditor Experience, Task Complexity, Locus Of Control, Obedience Pressure and Auditor Seniority.